Leaders produce leaders and managers produce followers: A systematic review of the desired competencies and standard settings for physicians’ leadership - Khoshhal, Khalid I.; Guraya, Salman Y. (Saudi medical journal, 2016)
To elaborate the desired qualities, traits, and styles of physician's leadership with a deep insight into the recommended measures to inculcate leadership skills in physicians. The databases of MEDLINE, EMBASE, CINAHL, and the Cochrane Library were searched for the full-text English-language articles published during the period 2000-2015. Further search, including manual search of grey literature, was conducted from the bibliographic list of all included articles. Medical Subject Headings (MeSH) keywords "Leadership" AND "Leadership traits" AND "Leadership styles" AND "Physicians' leadership" AND "Tomorrow's doctors" were used for the literature search. This search followed a step-wise approach defined by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The retrieved bibliographic list was analyzed and non-relevant material such as abstracts, conference proceedings, letters to editor, and short communications were excluded. Finally, 21 articles were selected for this review. The literature search showed a number of leadership courses and formal training programs that can transform doctors to physician leaders. Leaders can inculcate confidence by integrating diverse views and listening; supporting skillful conversations through dialogue and helping others assess their influence and expertise. In addition to their clinical competence, physician leaders need to acquire the industry knowledge (clinical processes, health-care trends, budget), problem-solving skills, and emotional intelligence. This review emphasizes the need for embedding formal leadership courses in the medical curricula for fostering tomorrow doctors' leadership and organizational skills. The in-house and off-campus training programs and workshops should be arranged for grooming the potential candidates for effective leadership.